Electrochemical Skin Conductance Correlates with Skin Nerve Fiber Density - Novak, Peter (Frontiers in Aging Neuroscience, 2016)
Purpose: Electrochemical skin conductance (ESC) using reverse iontophoresis and chronoamperometry has been used to evaluate abnormal function of small fibers. How ESC correlates with loss of small fibers in skin is unclear. Methods: This was a prospective, blinded study. The primary outcome measure was the correlation between ESC at the feet and results of skin biopsies including epidermal nerve fiber density (ENFD) and sweat gland nerve fiber density (SGNFD) at the distal leg. ESC, ENFD and SGNFD data were normalized by adjusting for weight. The secondary outcome measures were the correlation between ESC and the following variables: quantitative sudomotor axon reflex test (QSART) and symptom scales (neuropathy, pain and autonomic). Results: 81 patients ((mean±sd): age=53.3±17.3, men/women=25/56 were enrolled in the study. ESC was reduced in subjects with abnormally low ENFD (ENFD normal/abnormal, ESC = 1.17±0.27/0.87±0.34 µSiemens/kg, p<0.0008) and abnormally low SGNFD (SGNFD normal/abnormal ESC=1.09±0.34/,0.78±0.3 µSiemens/kg,p<0.0003). ESC correlated with ENFD (ρ=0.73, p=0.0001) and SGNFD (ρ=0.64, p=0.0001). ESC did not correlate with symptom scales. Conclusion: ESC is diminished in subjects who have a reduced number of small fibers in the skin and the ESC reduction is proportional to ENFD and SGNFD. ESC can be useful in detecting loss of small nerve fibers.